THE NEED FOR ENTREPRENEURSHIP AWARENESS TO BECOME AN ENTREPRENEUR! A CASE STUDY ON EMPOWERMENT OF ENTREPRENEURIAL ATTRIBUTES OF STUDENTS FROM A PRIVATE INSTITUTION OF HIGHER LEARNING - Bibi Noraini Mohd Yusuf; Noorkartina Mohamad; Farah Mastura Noor Azman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The entrepreneurial element has now emerged as one of the important pillars in designing appropriate attributes and structures of the academic curriculum covering varied disciplines in all fields of studies in Malaysia’s higher education institutions. This study was conducted in Perlis’s Islamic University College (KUIPs) campus aimed at understanding these attributes and the entrepreneurship cultural awareness of students’ in initiating and identifying appropriate entrepreneurial activities before completing their studies. The study was qualitative in nature involving a group of 20 students randomly chosen from four (4) faculties in KUIPs. Students were interviewed using instant message routes because of the restrictions imposed by authorities in addressing concerns a rising from the COVID 19 pandemic, where face-to-face interviews were disallowed due to health and security factors. The objectives of this study were 1) What are the factors that encourage students to become entrepreneurs on campus? and 2) What are the constraints facing students in becoming entrepreneurs on campus? The results of the study found that there were 3 main factors attributing to students’ keen interest to venture into entrepreneurial activities in KUIPs, namely a) keen interest to initiate own business and aspiring to be an entrepreneur after graduation, b) meeting students’ basic needs (social entrepreneurship), and c) able to earn extra income to defray living and study expenses. There were 3 constraints discovered in becoming entrepreneurs, namely a) Capital, b) Suitable Location, and c) Business Skills to start entrepreneurial activities (entrepreneurial knowledge/skills). The results of this study are most beneficial to those involved in the management of entrepreneurial affairs of students, students themselves, and lastly for the Faculty of Business and Management Sciences in KUIPs (in understanding the current attributes and constraints), there by enabling the faculty to design appropriate entrepreneurship programs and activities in order to nurture and create entrepreneurship cultural awareness for future students.